Mineralocorticoid Receptor Antagonist Use in Hospitalized Patients with Heart Failure, Reduced Ejection Fraction, and Diabetes Mellitus (from the EVEREST Trial) - Vaduganathan, Muthiah (2014)
Despite the well-established benefits of mineralocorticoid receptor agonists (MRAs) in heart failure with reduced ejection fraction, safety concerns remain in patients with concomitant diabetes mellitus (DM) because of common renal and electrolyte abnormalities in this population. We analyzed all-cause mortality and composite cardiovascular mortality and HF hospitalization over a median 9.9 months among 1,998 patients in the placebo arm of the Efficacy of Vasopressin Antagonism in Heart Failure Outcome Study With Tolvaptan (EVEREST) trial by DM status and discharge MRA use. Of the 750 patients with DM, 59.2% were receiving MRAs compared with 62.5% in the non-DM patients. DM patients not receiving MRAs were older, more likely to be men, with an ischemic heart failure etiology and slightly worse renal function compared with those receiving MRAs. After adjustment for baseline risk factors, among DM patients, MRA use was not associated with either mortality (hazard ratio [HR] 0.93; 95% confidence interval [CI] 0.75 to 1.15) or the composite end point (HR 0.94; 95% CI 0.80 to 1.10). Similar findings were seen in non-DM patients (mortality [HR 1.01; 95% CI 0.84 to 1.22] or the composite end point [HR 0.98; 95% CI 0.85 to 1.13] [p >0.43 for DM interaction]). In conclusion, in-hospital initiation of MRA therapy was low (15% to 20%), and overall discharge MRA use was only 60% (with regional variation), regardless of DM status. There does not appear to be clear, clinically significant in-hospital hemodynamic or even renal differences between those on and off MRA. Discharge MRA use was not associated with postdischarge end points in patients hospitalized for worsening heart failure with reduced ejection fraction and co-morbid DM. DM does not appear to influence the effectiveness of MRA therapy.